COMPARISON OF TRAMMEL NET FISHING RESULTSAT DAY AND NIGHT TIMEIN THE PRAPAT TUNGGAL VILLAGE, BENGKALIS DISTRICTRIAU PROVINCE - Nursahira Nursahira; Bustari Bustari; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe research aim to know comparison of day and night catches based on species, weight (kg), and individuals in trammel net fishing gear. The research method used is a survey method by direct observation of trammel net catches and then identified for fish species,  the number of individuals, and the weight of fish, then analyzed with, using a two-way T-test.  Descriptive results show that there are differences in day and night catches based on weight (kg) and number of individuals, where the most catches are found at night with the total weight of catches 26.1 kg and the number of individuals 653 tail Types of catches daytime and night  obtained the same consists of 7 types, namely gogo shrimp (Metapenaeus monoceras), tiger shrimp (Penaes monodon), layur fish (Thirchius savala), bilis fish (Mystacoleucus padangensis), puput fish (ilisha elongati), Gulamah fish (Johnius trachycephalus) and bleary fish (Mystacoleucus padangensis), puput fish (ilisha elongati), Gulamah fish (Johnius trachycephalus) and  crossbreed fish (Paraplotosus albilabris).Keywords :Trammel net ,comparison , Metapenaeus monoceras